2019
DOI: 10.1002/ceat.201800636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Elemental Quantification of Natural Hydroxyapatite Produced from Cow Bone

Abstract: The demand for hydroxyapatite (HA) is increasing annually due to the growing number of orthopedic patients, but it is a challenge to meet this growing demand without interfering with the integrity of the environment. Here, natural HA was produced from cow bone through ultrasound treatment followed by a calcination process at various temperatures. Characterization of the produced HA was performed by techniques such as thermogravimetric analysis, field emission scanning electron microscopy, Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…Ca, P and O, which are considered as key shares of hydroxyapatite, were observed in bone char with high percentages. The Ca/P ratio was found to be 2.02 in bone char, which was substantially equivalent to value 1.9 + 0.5, as presented by Akindoyo et al [34]. Lower value of Ca/P might be due to the alteration of amorphous structure of calcium and phosphorous [35].…”
Section: Sem Edx and Ftir Analysissupporting
confidence: 65%
See 1 more Smart Citation
“…Ca, P and O, which are considered as key shares of hydroxyapatite, were observed in bone char with high percentages. The Ca/P ratio was found to be 2.02 in bone char, which was substantially equivalent to value 1.9 + 0.5, as presented by Akindoyo et al [34]. Lower value of Ca/P might be due to the alteration of amorphous structure of calcium and phosphorous [35].…”
Section: Sem Edx and Ftir Analysissupporting
confidence: 65%
“…At 1750 cm −1 , the C = O stretch represents the esters group, while 1550 cm −1 and 1500 cm −1 represents the C = O and C = C stretch for RS-BC and WB-BC samples. Akindoyo et al [34] analyzed the IR spectrum of the prepared cow bone char and found peaks at 1411 and 1457 cm −1 , which indicates the presence of CO 3 −2 lattice in the HAP. Wu et al [37] and Peng et al [38] showed similar groups in RS-BC at wavenumber of 800-1600 cm −1 .…”
Section: Sem Edx and Ftir Analysismentioning
confidence: 99%
“…[37] The latter can also be attributed to the OH group of HA. [38] The bands associated with the amide-II groups of proteins (i.e., organic materials) are detected at 1240 and 1541 cm −1 , [39] and their weak contribution to the overall spectrum can be attributed to the partial denaturation and leakage of the proteins by the boiling pretreatment process. [40] Two other peaks are also attributed to the presence of organic materials present in the bone and are the symmetric and asymmetric stretching vibrations of the CH bond which appear at 2853 and 2922 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The E‐glass short fiber (length = 4.5 mm and diameter = 14 μm) was supplied by Lanxess AG, Cologne (Germany). On the other hand, the HA used was produced in our laboratory as previously described 26 …”
Section: Methodsmentioning
confidence: 99%